Fungsional Aditif Ortogonal pada W0(E) di dalam Rn - Riyadi, Riyadi (Journal of Mathematics and Mathematics Education, 2011)
AbstractThis paper discusses about a representation theorem of an orthogonally additive functional on W0(E)Ã M(E), that is a collection of all McShane integrable functions on a cell E=Â in Euclidean space Rn, which satisfies some certain properties. This result is a generalization of Chew result.Key words : orthogonally additive functional, McShane integrable, Euclidean space Rn.